The Effect of Quickness and Flexibility Training on Increasing The Reaction Time of The Sickle Kick in The Sport of Pencak Silat - Abelia Putri; Mulyana; Ivan Rivan Firdaus; Oktoviana Nur Ajid (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of quickness and flexibility training on increasing the reaction time of sickle kicks in pencak silat athletes. This study uses a quantitative approach with a one-group pretest-posttest quasi-experimental design. The subjects of the study were 16 pencak silat athletes from Banjaran Silat Club, Bandung Regency. Treatment was given through a quickness and flexibility training program for 12 sessions. The measurement instrument used a hit sensor kick shield pad connected to a digital application to measure the reaction time of sickle kicks. The results of statistical analysis showed that the data were normally distributed (p > 0.05) based on the Shapiro-Wilk test. The Paired Sample t-Test showed a significant difference between the pre-test and post-test values (t = 12.591, p = 0.000). The average reaction time value decreased from 0.58669 seconds to 0.49288 seconds after treatment. These findings indicate that the combination of quickness and flexibility training is effective in increasing the reaction time of sickle kicks. This research contributes to the development of a pencak silat training program based on neuromotor and body flexibility.